Treatment of a highly-concentrated sulphate-rich synthetic wastewater using calcium hydroxide in a fluidised bed crystallizer. (1st February 2018) - Maharaj, Chiara; Chivavava, Jemitias; Lewis, Alison
Abstract: This study aimed to investigate factors that affect the conversion of sulphates and magnesium, and the recovery of gypsum and magnesium hydroxide in the neutralization of a sulphate rich stream using calcium hydroxide, in a laboratory scale seeded fluidised bed crystallizer. Particular focus was on reducing the precipitated fines that escaped with the treated water, through the use of seeds, while removing as much sulphate-compounds from the waste stream as possible. The composition of the total sulphate salts was as follows: 80% magnesium sulphate, calcium sulphate remaining at its saturation concentration (1.5 g/L), with the remainder being sodium sulphate based on typical reverse osmosis retentate concentrations ranging from 1.5 – 120 g/L of total sulphate salts. The fluidised bed crystallizer, using silica seeds, was found to be effective at reducing the formation of gypsum and magnesium hydroxide fines by almost half. Feed concentrations of 35 g/L of total salts yielded better sulphate conversions (±75%), compared to a feed concentration of 8 g/L (±30%). It was possible to remove 99% of the magnesium in the saline wastewater stream using a calcium to sulphate ratio of 1:1 for feed concentrations of 15 g/L and higher. Excess calcium hydroxide suspension improved sulphate conversions. Highlights: A fluidised bed crystallizer is used to treat highly-concentrated, multi-component saline wastewater. A calcium hydroxide suspension is used to control supersaturation. The amount of fines exiting the reactor decreased in the presence of seeds. The configuration achieves 99% magnesium and 88% sulphate conversions.